Верхние оценки несбалансированности билинейных аппроксимаций раундовых функций блочных шифров - Алексейчук, А.Н.; Шевцов, А.С. (Кибернетика и системный анализ, 2010)
Досліджуються властивості раундових функцій блокових шифрів, що характеризують їх практичну стійкість відносно білінійного методу криптоаналізу. Отримано верхні межі незбалансованості білінійних апроксимацій раундових функцій шифрів, які містять ключовий суматор за модулем степеня числа 2, зокрема алгоритмів шифрування ГОСТ та «Калина». The raund functions properties of block ciphers that characterize practical security against bilinear cryptanalysis techniques are researched. Upper bounds of imbalance of bilinear approximations for raund functions of block ciphers with key adder modulo the degree of number 2, in particular, the encryption algorithms of the GOST and “Kalina” are obtained.